2003
DOI: 10.1086/374376
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the Antibody Response to the VlsE Sixth Invariant Region (IR6) Peptide ofBorrelia burgdorferiafter Successful Antibiotic Treatment of Lyme Disease

Abstract: It has been suggested that a <4-fold decline in the immunoglobulin G (IgG) antibody response to the VlsE sixth invariant region peptide of Borrelia burgdorferi within 6 months after antibiotic treatment may indicate spirochetal persistence in Lyme disease. We studied the response to this peptide in 77 patients with early or late disease, for whom archival samples were available at the time of antibiotic treatment and approximately 6 months or years later. Eight (33%) of the 24 patients with early manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 26 publications
5
46
2
2
Order By: Relevance
“…In a recent study of posttreatment persistence of the anti-C 6 antibody response in Lyme disease patients with both early and late disease, Peltomaa et al (18) reported results that at first glance appear squarely to contradict our findings. In a group of 15 patients with EM and 9 with facial paralysis, also an early sign of Lyme disease, the authors found that the anti-C 6 antibody reciprocal titer decreased Ͻ4-fold for 6 of 15 (40%) and 2 of 9 (22%) patients, respectively (8 of 24 [33%] for the group as a whole).…”
Section: Discussioncontrasting
confidence: 94%
“…In a recent study of posttreatment persistence of the anti-C 6 antibody response in Lyme disease patients with both early and late disease, Peltomaa et al (18) reported results that at first glance appear squarely to contradict our findings. In a group of 15 patients with EM and 9 with facial paralysis, also an early sign of Lyme disease, the authors found that the anti-C 6 antibody reciprocal titer decreased Ͻ4-fold for 6 of 15 (40%) and 2 of 9 (22%) patients, respectively (8 of 24 [33%] for the group as a whole).…”
Section: Discussioncontrasting
confidence: 94%
“…6,15 Furthermore, the detection of anti-C6 peptide antibodies is currently the only well-established test for confirming canine Lyme disease. 5,8 However, conflicting reports 7,12 of the ability of the C6 antibody test to discriminate active infection from past exposure have generated considerable confusion, especially when seropositive dogs fail to exhibit clinical abnormalities.…”
Section: Brief Communicationmentioning
confidence: 99%
“…After antibiotic treatment, antibody titers fall slowly, but IgG and even IgM responses may persist for years (96), as may the IgG response to the VlsE peptide (97). Moreover, asymptomatic IgG seroconversion to B. burgdorferi occurs in about 7% of patients in the US (98).…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%